Co-Creation Pada Tingkat Kunjungan Kedai Kopi di Bandung - Anti Riyanti; Andhika Chandra Lesmana (STIEPAR YAPARI Bandung, 2021)
Restaurant is a limitless industry, serving food and drinks to everyone near and far from their homes. It takes innovation and creativity in a business in order to continue to compete with other similar companies. Coffee shops are starting to grow and are mushrooming especially in big cities like Bandung. Co-creation is a term with the intention of allowing consumers to create shared value through collaboration their own desired drink which is expected to increase the level of visits at the coffee shop. This research was conducted in a period of less than one year, so the approach method used is a cross sectional method. Through this method with the aim of researchers being able to reveal and examine how much influence co-creation has in coffee shop consumer visits in Bandung. Based on the variables studied, the research method used is the quantitative method. The results show that Co-Creation is in the very high category and is an indication that the majority of respondents have a tendency to believe that all creative activities and social processes through collaboration between the coffee shop and their consumers have been carried out well. The level of visits is in the high category, this shows that respondents have high satisfaction so that it encourages buying behavior and loyalty. This means that a well co-creation will create the consumers to make visits and purchase attitudes.